2017
DOI: 10.1371/journal.pone.0175329
|View full text |Cite
|
Sign up to set email alerts
|

Acute development of cortical porosity and endosteal naïve bone formation from the daily but not weekly short-term administration of PTH in rabbit

Abstract: Teriparatide [human parathyroid hormone (1–34)], which exerts an anabolic effect on bone, is used for the treatment of osteoporosis in patients who are at a high risk for fracture. That the once-daily administration of teriparatide causes an increase in cortical porosity in animal models and clinical studies has been a matter of concern. However, it is not well documented that the frequency of administration and/or the total dose of teriparatide affect the cortical porosity. The present study developed 4 terip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 40 publications
2
33
0
Order By: Relevance
“…Endosteal bone apposition induced by PTH administration has been well documented in animal (39)(40)(41)67,69) and human studies, (70,71) and it has been suggested that this bone formation may be compensating for the increase in intracortical porosity to limit negative biomechanical effects. (41,72) We observed extensive endosteal bone formation for PTH, which uniquely had a trabecular-like appearance in 2D and 3D (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endosteal bone apposition induced by PTH administration has been well documented in animal (39)(40)(41)67,69) and human studies, (70,71) and it has been suggested that this bone formation may be compensating for the increase in intracortical porosity to limit negative biomechanical effects. (41,72) We observed extensive endosteal bone formation for PTH, which uniquely had a trabecular-like appearance in 2D and 3D (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The PTH dose used was intermediate to what has been utilized in recent studies analyzing the effects of PTH dosing regimens (10 μg/kg/d versus 40 μg/kg/d) on rabbit cortical bone. ( 39,42 ) The GC dose used was an intermediate‐to‐high dose (0.5 mg/kg/d versus 1.0 mg/kg/d versus 2.0 mg/kg/d) based on a previous study analyzing OVX and OVX + GC OP models in the rabbit. ( 44 ) SHAM and OVX received daily subcutaneous injections of 1 mL saline for the corresponding 4‐week dosing period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also reported in rabbits that the once-daily administration of teriparatide induced a marked increase in the cortical porosity, which was not observed following the once-weekly administration of equivalent total weekly doses. 26,27 Based on these previous studies, the shortening of dosing intervals to more than twice-weekly 28.2-μg injections in humans might induce the elevation of bone resorption markers, resulting in cortical porosity.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of the microstructure of the cortex of the tibia by micro‐ computed tomography or bone histomorphometry in rabbits show that the same total dose administered daily increased cortical porosity but not if administered weekly over 1 month. Newly deposited endosteal bone collagen fibres were well organized in the weekly regimen suggesting lamellar bone formation was normal but haphazard in the daily regimen . However, the mere demonstration of an increase in cortical porosity does not imply poorer bone quality, particularly since there are concomitant increases in periosteal and endosteal bone formation.…”
Section: Pharmacological Effects Of Pth – Use In Osteoporosis and Hypmentioning
confidence: 95%